Global Aging and Social, Cultural and Educational Needs of Elderly People ? a Challenge for the Third Age Universities - Zych, Adam A. (INSTED: Interdisciplinary Studies in Education & Society, 2012)
Global aging is becoming a major challenge for contemporary lifelong education and social systems that are aimed and/or designed to satisfy the changing social, cultural and educational needs of the outgoing generation. In order to satisfy them, a great number of educational, religious and governmental institutions, and even the media, can participate therein. If we are serious about fulfilling the basic mental, social, cultural and educational needs of the ?outgoing generation?, the current model of the university of the third age requires far-reaching changes and reforms, especially the spread of this idea on the European scale and a comprehensive programme and organization in order to satisfy such important human desires as the need to make sense of life, the need of self-realization, creativity, doing good and living an authentic, not simulated life, regardless old age, which is often seen as a painful shadow in arduous everyday reality.